2014
DOI: 10.11604/pamj.2014.19.178.3642
|View full text |Cite
|
Sign up to set email alerts
|

Mental health of doctors in a tertiary hospital in Nigeria

Abstract: IntroductionDoctors are vulnerable to psychiatric morbidity as a result of their busy schedules and multiple role obligations. Yet, they often don't admit they have mental health problems nor are they readily subjected to mental health evaluation by their colleagues due to fear of labeling and general stigma.MethodsA cross-sectional survey of doctors in the service of University of Ilorin Teaching Hospital, Ilorin, Nigeria was done using a socio-demographic questionnaire and the twelve items General Health Que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 20 publications
2
9
1
Order By: Relevance
“…Hours at work and sleep quality were significant factors that was related to higher scores on the GHQ. Similar findings have been reported by earlier research (11,14). In our study factors such as age, gender or type of specialty did not affect psychological morbidity as often reported in previous research (11).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Hours at work and sleep quality were significant factors that was related to higher scores on the GHQ. Similar findings have been reported by earlier research (11,14). In our study factors such as age, gender or type of specialty did not affect psychological morbidity as often reported in previous research (11).…”
Section: Discussionsupporting
confidence: 93%
“…Our findings mirrored what has been reported among Nigerian physicians. (11,12). Medical doctors have higher rate of psychological morbidity than what obtains in the general population (13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rate of psychological distress in the present study is several folds higher than the rates previously reported in the general population in similar contexts ( Erinfolami et al 2016 ; Gureje et al 2006 ). This study rate is also moderately higher than the rates previously reported in healthcare workers, 17.2% ( Obadeji et al 2018 ); doctors, 14.9% and 13.6% ( Issa et al, 2014 ; Ogunsemi et al 2019 ); and company executives, 14.2% in similar contexts using the same screening tool. While the rates of psychological distress in this study is moderately highly, it is conceivable that this estimate of psychological distress in healthcare workers may be conservative given the pervasive reluctance to disclose mental health problems due to stigmatization ( Knaak et al 2017 ; Yussuf and Balogun, 2006 ).…”
Section: Discussioncontrasting
confidence: 59%
“…10 Subsequent studies have all further confirmed the ability of the GHQ-12 to detect psychiatric morbidity in Nigeria. 1517 A cut-off score of ≥2 was used in this study to screen for those with psychiatric morbidity similar to previous studies from Nigeria. 10,12…”
Section: Methodsmentioning
confidence: 99%